Heart of a cowboy - Miller, Linda Lael.; Daniels, B.J.; Harlequin Books S.A. (Don Mills, Ontario : HQN Books, 2017)
Creed's honor. A descendant of the legendary McKettricks, Connor Creed knows exactly who he is: a hard working rancher carrying on his uncle's legacy in Lonesome Bend, Colorado. Small-town life isn't exactly his dream, but he owes a huge debt of gratitude to the man who took him in as a kid. When his identical twin, bad boy Brody Creed from whom Connor has been estranged for years, identity issues loom. Then Connor meets Tricia McCall, who knows a thing or two about living someone else's dreams. Together they might just find their own dreams in Lonesome Bend.
Unforgiven. When Destry Gran'ts brother is accused of killing Rylan West's sister, high school sweethearts Destry and Rylan leave their relationship behind in order to help their families recover from tragedy.
Creed's honor / Linda Lael Miller -- Unforgiven / B.J. Daniels.
Print version record.
Keywords: Cowboys -- Fiction; Ranchers -- Fiction; Man-woman relationships -- Fiction; Romance fiction; Western fiction; Electronic books